Analisis Risiko Gangguan Pembelajaran SMAN 12 Padang Akibat Banjir Bandang Desember 2025: Dampak, Mitigasi, dan Strategi Pemulihan - Naifa Filda Putri; Novita Maharani; Nurul Azizah; Reza Wulan Dari (GLOBAL SCIENTS PUBLISHER, 2025)
Flash floods are natural disasters that have the potential to cause serious disruptions to the continuity of the learning process, particularly in disaster-prone regions such as West Sumatra. This study aims to analyze the risk of learning disruption at SMAN 12 Padang as a result of the flash flood that occurred in December 2025, including risk identification, measurement of impact levels, and strategies for learning mitigation and recovery. The study employs a qualitative approach with a phenomenological design. Data were collected through semi-structured in-depth interviews with students and documentation studies of school archives and policies, and then analyzed thematically. The findings indicate that the risks of learning disruption originate from both external and internal school factors. The highest risks include damage to learning facilities and infrastructure, disruption of academic schedules, and students’ difficulties in adapting to emergency learning systems. Analysis using the Estimated Maximum Loss (EML) approach shows that damage to learning facilities has the most significant impact on the teaching and learning process. Mitigation efforts were carried out through facility restoration, the implementation of flexible academic policies, adjustments to learning methods, and psychosocial support for students. Recovery strategies are directed toward curriculum restructuring, remedial programs, enhancing teachers’ capacity, and strengthening collaboration with stakeholders. This study underscores the importance of disaster-based educational risk management in maintaining the resilience and sustainability of learning.